Giant dielectric response at low frequency of B-site modified Aurivillius oxide potassium bismuth titanate. (December 2018) - Fang, Pinyang; Zhi, Chongyang; Xi, Zengzhe; Long, Wei; Li, Xiaojuan
Graphical abstract: Highlights: K0.5 Bi4.5 Ti4- x (Al0.5 V0.5 ) x O12 ceramics were synthesized by the conventional solid-state reaction method. Giant dielectric response at low frequency were observed in the KBT-AlV ceramics. A giant dielectric constant (5.4 × 10 4 at 100 Hz) was obtained in the KBT-AlV specimens. Abstract: K0.5 Bi4.5 Ti4- x (Al0.5 V0.5 ) x O15 (KBT-AlV, x  = 0.00, 0.04, 0.06 and 0.08) ceramics were prepared by using the conventional solid-state reaction method. Phase analysis was performed by X-ray diffraction, and micro-structural morphology was assessed by scanning electron microscopy. The Effect of aluminium and vanadium on the structures, morphologies and electric properties of the K0.5 Bi4.5 Ti4 O12 (KBT) ceramics were investigated. Frequency dependence of the dielectric constant exhibited that the dielectric constant of the KBT ceramic is enhanced gradually by the aluminium and vanadium modification and a giant dielectric constant (5.4 × 10 4 at 100 Hz) can be observed in the KBT-AlV specimens. Moreover, the reasons for the giant dielectric constant of the KBT-AlV ceramics are discussed.